2018
DOI: 10.1007/s10068-018-0350-0
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of ultrasonic-assisted extraction of phenolic compounds from Justicia spicigera leaves

Abstract: A Box-Behnken design (Extraction-time, pulse-cycle, sonication-amplitude) was employed to extract phenolic compounds from leaves by ultrasonic-assisted extraction. The muicle leaves extracts were analyzed measuring total phenolic compounds and antioxidant capacity. According to response surface methodology the optimal conditions of ultrasonic-assisted extraction to obtain the highest soluble phenolic content were 2 min (extraction time) for 0.7 s (pulse cycle) at 55% of sonication amplitude. Under these optima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
40
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 32 publications
7
40
0
1
Order By: Relevance
“…In our study the yield of powder from raw garlic is about 26.68% which is closely relevant with the above mentioned studies. For GE preparation, here we used ultrasonic vibration for complete extraction from the sample because Altemimi et al, 2015 [20] and Anaya-Esparza et al, 2018 [35] studies have revealed that ultrasonic vibration increase the mean yield of plant extract and in our study we also obtained 50.25% total extract from crude powder that was a commendable yield of extraction.…”
Section: Discussionmentioning
confidence: 58%
“…In our study the yield of powder from raw garlic is about 26.68% which is closely relevant with the above mentioned studies. For GE preparation, here we used ultrasonic vibration for complete extraction from the sample because Altemimi et al, 2015 [20] and Anaya-Esparza et al, 2018 [35] studies have revealed that ultrasonic vibration increase the mean yield of plant extract and in our study we also obtained 50.25% total extract from crude powder that was a commendable yield of extraction.…”
Section: Discussionmentioning
confidence: 58%
“…However, the utility or potential of the UAE depends on factors such as: the type of metabolite, the raw material, or the food matrix. Therefore, research on optimization of metabolite extraction by UAE should be established for each plant product [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound (US) produces a phenomenon known as cavitation which contributes to the rupture of the cellular wall, the reduction of the pore size of solid materials, and an increase in the contact surface area between the solid phase and the solvent, facilitating the extraction of the components [13,14]. This technology was widely used for a great diversity of compounds [3,15,16], but not for the extraction of acetogenins. In a single study reported by Leon-Fernandez et al [17], they found that the use of ultrasonic bath at 42 kHz for 3 h increased the qualitative extraction of acetogenins from soursop pulp compared to extraction by maceration, soxhlet method, and microwaves; however, further trials are required using an ultrasonic equipment with direct application, evaluating factors of amplitude, extraction time, temperature, and ultrasonic cycles (pulse-cycles), to optimize the extraction in different raw materials and different bioactive compounds [18].…”
Section: Introductionmentioning
confidence: 99%